3D nano-network structured SiCN ceramic aerogels on mullite fiber felts for electromagnetic wave absorption. Issue 23 (1st December 2022) - You, Guiqin; Han, Daoyang; Tian, Huijie; Liang, Junfang; Wang, Chang-An; Yuan, Keke; Li, Mingliang; Wang, Hailong; Zhang, Rui; Shao, Gang
Abstract: Mullite fiber heat insulation tile is extensively used in thermal protection system (TPS) of aircrafts due to its excellent thermal insulation and chemical stability. However, there is a lack of research on the design of its microwave absorption function, which can affect aircraft safety and service efficiency. In this study, mullite fiber felts were used as framework to impregnate polysilazane. After sol-gel and high-temperature pyrolysis processes, SiCN microwave absorption ceramics with 3D nano-network structure were prepared on mullite fibers (SiCN/mullite composites). By controlling pyrolysis temperature from 800°C to 1200°C, the microstructure, dielectric properties, and microwave absorption properties of SiCN/mullite composites in the range of 2–18 GHz were regulated. Findings show that when pyrolysis temperature was 1000°C, microwave absorption properties of SiCN/mullite composites were better. Their minimum reflection loss value reached −39.38 dB at 12.08 GHz and the absorption bandwidth almost covered the whole X-band. Therefore, microwave absorption function of mullite fibers based on heat insulation property is of strategic significance for TPS.